1971
DOI: 10.1017/s0043174500050530
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxylation of 2,4-D in Several Weed Species

Abstract: Wild buckwheat (Polygonum convolvulus L.), leafy spurge (Euphorbia esula L.), yellow foxtail [Setaria glauca (L.) Beauv.], and wild oat (Avena fatua L.) hydroxylated, in a 7-day period, 2 to 7% of the (2,4-dichlorophenoxy)acetic acid-1-14C (2,4-D-1-14C) absorbed. Only a trace of hydroxylation products was detected in wild mustard [Brassica kaber (DC.) L. C. Wheeler var. pinnatifida (Stokes) L. C. Wheeler], perennial sowthistle (Sonchus arvensis L.), and kochia [Kochia scoparia (L.) Roth]. The investigation was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1973
1973
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…The ring-hydroxylated metabolites, which do not possess growth stimulatory activity, were identified as 4-hydroxy-2,5-dichlorophenoxyacetic acid (4-OH-2,5-D) and 4-hydroxy-2,3-dichlorophenoxyacetic 2,3-D). These two metabolites were previously found in bean and other plants by Thomas et al (1964), Hamilton et al (1971), andFleeker andSteen (1971). Faulkner and Woodcock (1964) identified 4-OH-2,5-D as a metabolite in Aspergillus niger.…”
Section: Tablesupporting
confidence: 58%
“…The ring-hydroxylated metabolites, which do not possess growth stimulatory activity, were identified as 4-hydroxy-2,5-dichlorophenoxyacetic acid (4-OH-2,5-D) and 4-hydroxy-2,3-dichlorophenoxyacetic 2,3-D). These two metabolites were previously found in bean and other plants by Thomas et al (1964), Hamilton et al (1971), andFleeker andSteen (1971). Faulkner and Woodcock (1964) identified 4-OH-2,5-D as a metabolite in Aspergillus niger.…”
Section: Tablesupporting
confidence: 58%
“…Very little work has been performed on 2,4-D metabolism in the Brassicaceae family, and no study has detected the glucose ester. In an investigation targeting hydroxylated 2,4-D metabolites, trace levels of 4-OH-2,5-D were found in 2,4-D-treated wild mustard (Brassica kaber) . In a study focused on the potential for amino acid conjugation of 2,4-D in Arabidopsis thaliana, small amounts of the aspartyl and glutamyl 2,4-D amides were isolated .…”
Section: Discussionmentioning
confidence: 99%
“…This is, to our knowledge, the first reported NMR analysis of 2,4-D glucose ester isolated from a biological extract and . 27 In a study focused on the potential for amino acid conjugation of 2,4-D in Arabidopsis thaliana, small amounts of the aspartyl and glutamyl 2,4-D amides were isolated. 15 Wild radish may also produce low levels of the aspartyl amide of 2,4-D based on the mass spectral characteristics of a minor metabolite examined in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Prelitninary trials by the authors (data not shown) established that 96% of the applied radioactivity was recovered following the application of I-lC-2,4-D. However, because 2,4-D can be rapidly Inetabolized after absorption into plant tissue (Fang 1958;Fleeker and Steen 1971), we are uncertain as to whether recovered radioactivity represented parent 2,4-D, 11letabolized 2,4-0, or both. Recovery of radioactivity following the application of I-lC-2,4-0B was 950/0.…”
mentioning
confidence: 98%